MODEL PENGHITUNGAN ZAKAT PERTANIAN PADA PETANI PADI MENURUT HUKUM ISLAM (STUDI KASUS DI KECAMATAN MARIORAWA KABUPATEN SOPPENG) - Andi Achruh; Iqbal, Muhammad (Inspiratif Pendidikan, 2024)
This qualitative descriptive study explores the practices and understanding of zakat, specifically agricultural zakat, among rice farmers in Kecamatan Marioriawa, Kabupaten Soppeng, South Sulawesi. Utilizing a phenomenological, syar’i, and juridical approach, the research focuses on how these farmers interpret and implement the Islamic obligation of zakat. Data were collected through interviews, observations, and document analysis, following an interactive method of data analysis. The study reveals a significant gap between the theoretical principles of zakat in Islam and its practical application among the farmers. Many do not accurately understand the regulations concerning nisab (the minimum amount of agricultural produce that necessitates the payment of zakat), haul (the period for zakat collection), and the percentage of zakat to be given. This misunderstanding results from inadequate education and mobilization efforts by local zakat management authorities and religious leaders. The research further discusses the variations in zakat practices, with some farmers calculating zakat incorrectly or choosing zakat recipients subjectively. This discrepancy highlights the urgent need for better education and a more proactive approach from zakat collectors (amil zakat) in educating and collecting zakat from rice farmers. The study suggests that local government and religious institutions should collaborate to provide training and workshops to enhance farmers’ understanding and proper practice of zakat according to Islamic teachings. Additionally, the formation of village or sub-district zakat teams is recommended to facilitate the collection and distribution of zakat in a more structured, transparent, and accountable manner, ensuring the optimal function of zakat as a tool for economic empowerment and poverty alleviation in the community.